2023
DOI: 10.3390/diagnostics13111882
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of p-ANCA Positivity in Idiopathic Pulmonary Fibrosis: A Retrospective Observational Study

Abstract: Perinuclear Anti Neutrophil Cytoplasmic Antibody (p-ANCA) is a serological marker of Microscopic Polyangiitis (MPA), a vasculitis associated with lung involvement potentially mimicking Idiopathic Pulmonary Fibrosis (IPF). In this study, we evaluated the role of p-ANCA in predicting clinical evolution and prognosis in a cohort of IPF patients. In this observational, retrospective, case–control study, we compared 18 patients with an IPF diagnosis and p-ANCA positivity with 36 patients with seronegative IPF, matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…According to Libra et al, evaluating the role of p-ANCA in predicting clinical evolution and prognosis in a cohort of IPF patients revealed similar lung function decline in IPF patients with and without p-ANCA during follow-up. However, IPF p-ANCA + showed better survival 21 . Similarly, our study showed that the survival was better in ANCA-UIP than IPF.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…According to Libra et al, evaluating the role of p-ANCA in predicting clinical evolution and prognosis in a cohort of IPF patients revealed similar lung function decline in IPF patients with and without p-ANCA during follow-up. However, IPF p-ANCA + showed better survival 21 . Similarly, our study showed that the survival was better in ANCA-UIP than IPF.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, a few previous studies have investigated serial changes in clinical symptomatology, PFT results, and HRCT findings in patients with MPA-ILD or ANCA-IP 20 , 21 . Our study found a relatively high incidence where approximately 40% of patients with ANCA-ILD demonstrated PPF.…”
Section: Discussionmentioning
confidence: 99%
“…In this special issue, three articles reported on interstitial lung disease, confirming that this is a hot topic in respiratory research [ 6 , 7 , 8 ]. In the first study, the authors conducted an observational, case–control, retrospective study to evaluate the role of the perinuclear anti-neutrophil cytoplasmic antibody (p-ANCA) in predicting clinical evolution and prognosis in patients with idiopathic pulmonary fibrosis (IPF) [ 6 ]. The researchers enrolled 18 IPF p-ANCA-positive patients and 36 IPF p-ANCA-negative patients.…”
mentioning
confidence: 82%
“…Interestingly, the paper showed that p-ANCA positivity, especially when associated with high levels of rheumatoid factor (RF), could predict the evolution of usual interstitial pneumonia (UIP), with a better prognosis than IPF. In conclusion, it is important to emphasise that ANCA testing should be included in the diagnostic routine of patients with UIP to help clinicians in the evaluation and follow-up of these complicated patients [ 6 ].…”
mentioning
confidence: 99%
“…Patients initially diagnosed with idiopathic pulmonary fibrosis (IPF) may have positive ANCAs, particularly MPO-ANCAs, during the course of the disease, found in 8.5% of them at presentation, while after five years, 24.3% of them will eventually develop other features of MPA [43]. A retrospective study conducted in North America, including 745 patients with IPF, demonstrated that 25-33% of patients who were initially diagnosed with IPF and MPO-ANCA positivity developed vasculitis symptoms within a median follow-up period of 18 months [44].…”
Section: Gpa and Mpamentioning
confidence: 99%